2020
DOI: 10.33483/jfpau.586590
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Detailed Characterization of Voriconazole Loaded in Situ Gels for Ocular Application

Abstract: Objective: This study was aimed to prepare, characterize and evaluate in situ gel formulation for a sustained ocular delivery of voriconazole. Material and Method: In situ gels were prepared with three different hydrophilic co-polymers: Poloxamer 188, 407 and 388. The formulations were characterized in terms of their clarity, pH, viscosity drug content uniformity and mechanical/rheological properties. Moreover, in vitro drug release and stabilitystudies were performed. Result and Discussion: The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…With an increase in shear strain the viscosity decreases, as seen in shear thinning. Our findings demonstrated sheer thinning at 37±0.1ºC, in line with the literatures [26][27][28][29]. In our study the G8 formulations gave rise to the highest viscosity value and had the most consistent gel structure.…”
Section: Rheological Studiessupporting
confidence: 92%
“…With an increase in shear strain the viscosity decreases, as seen in shear thinning. Our findings demonstrated sheer thinning at 37±0.1ºC, in line with the literatures [26][27][28][29]. In our study the G8 formulations gave rise to the highest viscosity value and had the most consistent gel structure.…”
Section: Rheological Studiessupporting
confidence: 92%
“…The optimized in situ gel underwent gelation within 1.233 ± 0.058 s at 32.200 ± 0.265 • C. Particularly, the addition of poloxamer 188 lengthened the gelation time and increased the gelling capacity. Similar in vitro release study results were observed in which the formulations showed sustained release up to 24 h [34]. Nonetheless, in vivo studies for ocular irritation and retention, and ex vivo permeation studies had not been conducted in this study compared to the previous study.…”
Section: Ocular Fungal Infectionssupporting
confidence: 80%
“…Nonetheless, in vivo studies for ocular irritation and retention, and ex vivo permeation studies had not been conducted in this study compared to the previous study. In addition, both studies [ 33 , 34 ] had not conducted in vivo antimicrobial efficacy to show the potential clinical use of the novel formulations.…”
Section: Smart Ocular Delivery Using Stimuli-responsive In Situ Gel Platformmentioning
confidence: 99%
“…2 ml of sample was taken at a predetermined times from 30 min to 48 h and the same volume of fresh medium was replaced. The samples were analyzed with UV for determination of the drug content [36].…”
Section: In Vitro Release Studiesmentioning
confidence: 99%